2021
DOI: 10.1186/s12885-021-07783-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ICAM-1, CCL2 and TGM2 gene polymorphisms on differentiation syndrome in acute promyelocytic leukemia

Abstract: Background Although arsenic trioxide (ATO) and all-trans retinoic acid (ATRA) are well-tolerated and effective treatments for Acute Promyelocytic Leukemia (APL), Differentiation Syndrome (DS) is a lethal side effect in some patients. The pathogenesis of DS is complex and not well understood; however, it is considered as an inflammatory response due to cytokines release of differentiated cells. Moreover, adhesion molecules that are widely expressed on the surface of differentiated cells and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…However, several patient may experience DS (21). Although the pathogenesis of DS remains to be elucidated, mounting evidence has suggested that sustained hyperinflammation serves a critical role in its pathogenesis (16,21,22). The current study showed that PADI4 could serve an essential role in regulating the expression of inflammatory cytokines, such as TNF-α and IL-1β, in ATRA-treated NB4 cells.…”
Section: Discussionmentioning
confidence: 54%
“…However, several patient may experience DS (21). Although the pathogenesis of DS remains to be elucidated, mounting evidence has suggested that sustained hyperinflammation serves a critical role in its pathogenesis (16,21,22). The current study showed that PADI4 could serve an essential role in regulating the expression of inflammatory cytokines, such as TNF-α and IL-1β, in ATRA-treated NB4 cells.…”
Section: Discussionmentioning
confidence: 54%
“…Уровень этого фермента коррелировал с экспрессией молекул адгезии и рядом апоптотических белков [113]. В другом исследовании на образцах пациентов с острым промиелоцитарным лейкозом продемонстрирована положительная корреляция между экспрессией TG2 и синдромом дифференцировки, возникающим при терапии триоксидом свинца и транс-ретиноевой кислотой [114].…”
Section: Methodsunclassified
“…When it is not rapidly diagnosed and treated, APL is considered one of the worst leukemias [ 93 ]. In the context of canonical APL treatment with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO), TG2 expression is increased, and this leads to an intensification of inflammation through the NF-κB pathway [ 94 ]. Consequently, TG2 inhibition reduces ROS production, inflammation processes, and consequent organ damage [ 95 ].…”
Section: Tg2 In Cancermentioning
confidence: 99%
“…Consequently, TG2 inhibition reduces ROS production, inflammation processes, and consequent organ damage [ 95 ]. To turn off the lethal effects of the inflammatory response (called differentiation syndrome, it is typically present after ATRA-ATO treatment [ 96 ]) is crucial to improving patient outcome [ 94 ]. Moreover, Jambrovics K et al highlight the mechanism through which TG2 is able to extend APL cell survival following conventional ATRA-ATO treatment.…”
Section: Tg2 In Cancermentioning
confidence: 99%